Reconciling Consumer and Vendor Preferences for Food Safety Attributes in Dhaka Wet Markets, Bangladesh - Mulwa, Chalmers K.; Prain, Gordon; Okumu, Boscow; Malit, Jack; Ibrahim, Farhana; Alonso, Silvia; Moyo, Mukani (SSRN, 2025)
Rapid urbanization presents major challenges to urban food systems, impacting access to safe and nutritious food especially in developing countries. With the urban demand for food surging, there is a proliferation of largely unregulated vendors in the informal food sector to meet this demand. However, these vendors often work in market environments characterized by inadequate sanitation infrastructure and poor waste management processes. Coupled with low consumer and vendor awareness on food safety, this presents a high risk for the spread of foodborne diseases and a significant threat to public health. To understand both demand-and supply-side policy options for promoting food safety, this study utilizes a choice experiment approach to investigate the interplay between consumer preferences and vendor practices regarding food safety in Dhaka's urban markets. The study finds that consumers favour high-quality fresh produce and prioritize vendors with good hygiene, as well as markets with medium to high sanitation. Conversely, vendors have high preferences for markets with improved sanitation and permanent infrastructure, but show hesitation towards investments in storage improvements, underlining the need for targeted policy interventions. Both consumers and vendors have a high willingness to pay for improved market conditions that promote food quality and safety, suggesting that improving market sanitation infrastructure and establishing permanent structures to maintain the quality of fresh produce could be mutually beneficial for both types of actors. Additionally, enhancing food safety awareness among both parties is imperative, addressing the prevalent disregard for vendor hygiene and its repercussions for public health.